BASCO: a toolbox for task-related functional connectivity - Göttlich, Martin; Beyer, Frederike; Krämer, Ulrike (Frontiers in Systems Neuroscience, 2015)
BASCO (BetA Series COrrelation) is a user-friendly MATLAB toolbox with a graphical user interface which allows investigating functional connectivity in event-related functional magnetic resonance imaging (fMRI) data. Connectivity analyses extend and compliment univariate activation analyses since the actual interaction between brain regions involved in a task can be explored. BASCO supports seed-based functional connectivity as well as brain network analyses. Although there are a multitude of advanced toolboxes for investigating resting-state functional connectivity, BASCO is the first toolbox for evaluating task-related whole-brain functional connectivity employing a large number of network nodes. Thus, BASCO allows investigating task-specific rather than resting-state networks. Here, we summarize the main features of the toolbox and describe the methods and algorithms.